2015
DOI: 10.4103/2229-5151.170846
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative sciatic and femoral or saphenous nerve blockade for lower extremity surgery in anesthetized adults

Abstract: Background:Guidelines warn of increased risks of injury when placing regional nerve blocks in the anesthetized adult but complications occurred in patients that received neither sedation nor local anesthetic. This restriction of nerve block administration places vulnerable categories of patients at risk of severe opioid induced side effects. Patient and operative technical factors can preclude use of preoperative regional anesthesia. The purpose of this study was to assess complications following sciatic popli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In the present study, none of the patients exhibited motor blockade. Lollo et al [7] demonstrated a similar standard that all patients should be able to perform toe plantar flexion immediately and after 24 hours postoperatively. The importance of any clinical study is based on patient satisfaction, and in this study, there was showed no statistical difference in PSS in the three groups at 24 and 48 hours postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, none of the patients exhibited motor blockade. Lollo et al [7] demonstrated a similar standard that all patients should be able to perform toe plantar flexion immediately and after 24 hours postoperatively. The importance of any clinical study is based on patient satisfaction, and in this study, there was showed no statistical difference in PSS in the three groups at 24 and 48 hours postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Use of combined femoral and sciatic blocks offer a practical alternative to epidural analgesia for unilateral knee replacements [6]. Lollo et al [7] reported no major nerve injury or deficit among 357 popliteal sciatic nerve blocks with either femoral or saphenous nerve blocks performed. YaDeau et al [8] compared ultrasound-guided sciatic and adductor canal blocks (ACB) with intravenous (IV) dexamethasone and/or buprenorphine, and found there was no difference in pain with movement at 24 hours.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Past literature reports minimal risk and low complication rates of peripheral nerve blocks in studies with large sample sizes (10,12).…”
Section: Discussionmentioning
confidence: 99%
“…Provenzano et al did not report any complications affiliated with peripheral nerve blocks in a group of 467 patients that underwent foot and ankle surgery (6). Similarly, Lolo et al did not report any major nerve injury or deficit after the administration of 357 nerve blocks in the lower extremity (12). Meanwhile, Anderson et al reported a cohort of 1014 patients where 52 patients (5%) had neuropathic symptoms postoperatively likely related to popliteal block, excluding patients with complex regional pain syndrome and neurologic-symptoms related to procedure (5).…”
Section: Discussionmentioning
confidence: 99%